PERJANJIAN WESTPHALIA DAN MOMENTUM PENDIRIAN NEGARA MODERN - Amsir, Ahmad Abdi (Sulesana: Jurnal Wawasan Keislaman, 2021)
The Treaty of Westphalia in 1648 opened a new history for the political constellations of Europe and the world. Based on the results of the Westphalia agreement, the legal concept of sovereignty of the nation-state (state-nation) and the institutionalization of military power and diplomacy were mutually agreed upon by the rulers in Europe through consensus. After the emergence of the Westphalia Treaty, the new structure of the international community was based on national states and was no longer based on kingdoms, empires, and churches. In addition, the composition of the international community is also based on the nature of the state together with its government, which is to separate state power and government from the influence of the church. Various changes in the post-Westphalia international relations system include the growth of representative government, the occurrence of the industrial revolution, the development of international law, the development of diplomacy methods in addition to military strategy, the growth of interdependence among nation states in the economic field, and the birth of procedures - procedures for resolving conflicts peacefully. In short, the Westphalia Treaty has laid the foundation for this form and nature in the composition of the new international community.